Manajemen Airway pada Pembedahan Laminectomy dengan General Anestesi Endotracheal Tube (ETT) - Serli Ayuning Tias; Rio Kristian Nugroho (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Laminectomy surgery requires optimal airway management due to the prone position of the patient. General anesthesia using Endotracheal Tube (ETT) is commonly used to maintain airway patency and adequate ventilation throughout the procedure. This is a descriptive observational study involving five patients with lumbar spinal stenosis who underwent laminectomy surgery under general anesthesia with ETT at RSUD Pandan Arang Boyolali. All patients were successfully intubated with nom kinking ETT using the MILI technique and video laryngoscope. During surgery, ventilation and hemodynamics remained stable with continuous monitoring of ETCO₂, SpO₂, MAP, and CVP. No major airway complications were reported. A systematic airway management approach using non kinking ETT, MILI technique, and invasive monitoring proved safe and effective for laminectomy surgery in the prone position.